Analisis Kinerja Kompresor Gas Reciprocating C-401 Menggunakan Metode Kenaikan Enthalpy Di PT. Energi Mega Persada - Rahmad Fauzi; Syafri Syafri; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In heavy lifting equipment that works pneumatically, the compressor is used in its function as an air filling device for power sources. A compressor when viewed from the way it works, there are two types of compressors, each of which works differently. The first type is a compressor with a positive displacement work method and the second is a compressor with a dynamic working method. Where the difference between the two types is the first positive displacement type compressor, this compressor model works by inserting air into a closed space, then at the same time the volume of the space is reduced, then the pressure inside will naturally increase. This high pressure which is used for various purposes in accordance with the designation of the compressor. This positive displacement compressor is used in reciprocating compressors and rotary. Meanwhile on the dynamic model compressor, the volume of space is fixed but the air inside the space is given speed. Then at the same time the speed is changed to pressure. This happens because the air in the room whose volume is still under pressure. Compressors that use this dynamic model are usually on turbo axial flow devices. Reciprocating gas compressors located at PT. Energi Mega Persada (EMP) Riau, has experienced a decline in performance, causing the performance of the compressor gas to be not optimal in compressing gas.Keywords: Enthalpy Rise Method, Reciprocating Gas Compressor, Peformance Decrease.